Penggunaan Jerami Padi Amoniasi Fermentasi (Amofer) Pada Sapi Bali - Sofyan Damrah Hasan; Oscar Yanuarianto; Mohammad Iqbal; Muhamad Amin (Jurnal Ilmu Dan Teknologi Peternakan Indonesia (JITPI) Indonesian Journal of Animal Science and Technology), 2018)
An experiment to study the effect of using ammoniated and fermented rice straw (Amofer) in ration on performance of Bali cattle was conducted at the Laboratory of Nutrition and Feed of Animal Husbandry Faculty, Mataram University. This research was carried out for 8 months, started on April to November 2014. The research materials were four male of Bali cattle and rice straw Amofer. The experiment was designed in 4 x 4 Latin Square with 4 heads of Bali cattle, 4 types of diets as treatments, and 4 periods as replications. The variables measured were feed intake, digestibility, average daily gain, and feed efficiency. All data were analyzed with analysis of variance, and tested further by Duncan’s Multiple Range Test. The results of research showed that treatments did not have significant effect (P>0,05) on feed intake, digestibility, average daily gain, and feed efficiency.